2020
DOI: 10.3390/nu12092898
|View full text |Cite|
|
Sign up to set email alerts
|

KiwiC for Vitality: Results of a Placebo-Controlled Trial Testing the Effects of Kiwifruit or Vitamin C Tablets on Vitality in Adults with Low Vitamin C Levels

Abstract: Consumption of vitamin C-rich fruit and vegetables has been associated with greater feelings of vitality. However, these associations have rarely been tested in randomized controlled trials. The aim of the current study was to test the effects of eating a vitamin C-rich food (kiwifruit) on subjective vitality and whether effects are driven by vitamin C. Young adults (n = 167, 61.1% female, aged 18–35) with plasma vitamin C <40 µmol/L were randomized into three intervention conditions: kiwifruit (2 SunGold™ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(65 citation statements)
references
References 66 publications
4
60
0
Order By: Relevance
“…Participants were recruited during screening for the KiwiC for Vitality Intervention Study (see Conner et al, 2020)) [9]. The trial was preregistered with the Australian and New Zealand Clinical Trial Registry (Trial ID: ACTRN12617001031358) and approved by the New Zealand Health and Disability Ethics Committee (17/NTB/104).…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants were recruited during screening for the KiwiC for Vitality Intervention Study (see Conner et al, 2020)) [9]. The trial was preregistered with the Australian and New Zealand Clinical Trial Registry (Trial ID: ACTRN12617001031358) and approved by the New Zealand Health and Disability Ethics Committee (17/NTB/104).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Psychological measures were added to the screening protocol for the second wave of recruitment and these participants were included in this analysis. For full protocol and methods used, see Conner et al (2020) [9]. Recruitment for the present dataset began in February 2018 and ended in April 2018, and used advertisements placed around the University of Otago and Otago Polytechnic campuses in Dunedin, New Zealand.…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…
We read the report by Conner and colleagues that tested whether kiwifruit or vitamin C affected measures of vitality [1]. The trial is reported as a randomized controlled trial (RCT), but not all participants were allocated randomly, and some participants were group-randomized, which was not accounted for in the analysis.
…”
mentioning
confidence: 99%